Planform architecture, stratigraphic signature and morphodynamics of an exhumed Jurassic meander plain (Scalby Formation, Yorkshire, UK). Issue 7 (30th June 2014) - Ielpi, Alessandro; Ghinassi, Massimiliano; Mountney, Nigel
Abstract Modern fluvial meander plains exhibit complex planform transformations in response to meander‐bend expansion, downstream migration and rotation. These transformations exert a fundamental control on lithology and reservoir properties, yet their stratigraphic record has been poorly evaluated in ancient examples due to the lack of extensive three‐dimensional exposures. Here, a unique exhumed meander plain exposed to the north of Scarborough (Yorkshire, UK) is analysed in terms of architecture and morphodynamics, with the aim of developing a comprehensive model of facies distribution. The studied outcrop comprises tidal platforms and adjacent cliffs, where the depositional architecture of un‐tilted deposits was assessed on planform and vertical sections, respectively. In its broader perspective, this study demonstrates the potential of architectural mapping of extensive planform exposures for the reconstruction of ancient fluvial morphodynamics. The studied exhumed meander plain is part of the Scalby Formation of the Ravenscar Group, and originally drained small coastal incised valleys within the Jurassic Cleveland Basin. The meander plain is subdivided into two storeys that contain in‐channel and overbank architectural elements. In‐channel elements comprise expansional and downstream‐migrating point bars, point‐bar tails and channel fills. Overbank elements comprise crevasse complexes, levées, floodplain fines and lake fills. The evolution of the point bars played a significant role in dictating preserved facies distributions, with high flood‐stage nucleation and accretion of meander scrolls later reworked during waning flood‐stages. At a larger scale, meander belt morphodynamics were also a function of valley confinement and contrasts in substrate erodibility. Progressive valley infilling decreased the valley confinement, promoting the upward transition from prevalently downstream migrating to expansional meander belts, a transition associated with enhanced preservation of overbank elements. Strikingly similar relations between valley confinement, meander‐bend transformations and overbank preservation are observed in small modern meandering streams such as the Beaver River of the Canadian prairies and the Powder River of Montana (USA).